Mathematical Simulation of Heat Generation at a Cutting-Tool Surface During Stock Removal Processes - MZAD, Hocine (Engineering Transactions, 2021)
The heat generated in various cutting zones significantly influences machining, affects tool wear, and thereby reduces tool life. In this paper, a spline cubic interpolation is used to estimate the transient heat flux imposed on the surface of a carbide cutting tool during stock removal, at constant thermal properties and cutting velocity. Interpolation of instantaneously measured temperature data set by the polynomial of lowest possible degree that passes through the points of the dataset is obtained. A high-precision remote-sensing infrared thermometer is used to measure the temperature at the surface. For friction shear stress determination, a mounted sensing system detects strain gauges signals and computes them in the form of forces on the display screen. From thermal behavior point of view the final result is notably interesting: it highlights the feature of non-proportionality in temperature/heat flux variation.